The effects of urbanization on pollinators and pollination: A meta‐analysis - Liang, Huan; He, Yong‐Deng; Theodorou, Panagiotis; Yang, Chun‐Feng (Ecology letters, 2023)
Urbanization is increasing worldwide, with major impacts on biodiversity, species interactions and ecosystem functioning. Pollination is an ecosystem function vital for terrestrial ecosystems and food security; however, the processes underlying the patterns of pollinator diversity and the ecosystem services they provide in cities have seldom been quantified. Here, we perform a comprehensive meta‐analysis of 133 studies examining the effects of urbanization on pollinators and pollination. Our results confirm the widespread negative impacts of urbanization on pollinator richness and abundance, with Lepidoptera being the most affected group. Furthermore, pollinator responses were found to be trait‐specific, with below‐ground nesting and solitary Hymenoptera, and spring flyers more severely affected by urbanization. Meanwhile, cities promote non‐native pollinators, which may exacerbate conservation risks to native species. Surprisingly, despite the negative effects of urbanization on pollinator diversity, pollination service measured as seed set is enhanced in non‐tropical cities likely due to abundant generalists and managed pollinators therein. We emphasize that the richness of local flowering plants could mitigate the negative impacts of urbanization on pollinator diversity. Overall, the results demonstrate the varying magnitudes of multiple moderators on urban pollinators and pollination services and could help guide conservation actions for biodiversity and ecosystem function for a sustainable future. Urbanization is increasing worldwide, with major impacts on biodiversity and ecosystem service. Our meta‐analysis of 133 studies examining urbanization effects on pollinators and pollination showed that the magnitudes of the effects were dependent on the taxonomic group of the pollinator, its origin and functional traits. Despite pollinator decline in non‐tropical cities, pollination services measured as seed sets are enhanced.